The Family Gap for Young Women in the United States and Britain: Can Maternity Leave Make a Difference? - Waldfogel, Jane (Journal of Labor Economics, 1998)
In the United States and Britain, there is a "family gap" between the wages of mothers and other women. Differential returns to marital and parental status explain 40%–50% of the gender gap. Another 30%–40% is explained by women's lower levels of work experience and lower returns to experience. Taking advantage of "quasi experiments" in job‐protected maternity leave in the United States and Britain, this article finds that women who had leave coverage and returned to work after childbirth received a wage premium that offset the negative wage effects of children.